20 Designers. - Dehaybe, Roger; Loze, Pierre (Köln : Das Belgische Haus Köln, 1997)
Baudoux, Olivier ; Bauwens, Pascal ; Mauritz, Bert ; Brasseur, Frédéric ; Chennaux, Alain ; de Monge, Ladislas ; De Wulf, Claude ; Fettweis, Baudouin ; Kuku, Ola-Dele ; Kümel, Lydia ; Lallemand, Pierre ; Lust, Xavier ; Ménager, Claire ; Michaux, Henriette ; Balboa, Ricky ; Quadens, Pol ; Sarfati, Franck ; Scuvée, Romano ; Seleck, François ; Szpirer, Vincent
biografie
Frans
boek